2022
DOI: 10.14202/vetworld.2022.2442-2452
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and resistance to gastrointestinal parasites in goats: A review

Abstract: Gastrointestinal parasitism, particularly nematode infection, is a major health issue affecting goats worldwide, resulting in clinical diseases and productivity loss. Prevalent gastrointestinal parasites (GIPs) affecting goats in South Africa are the Strongyloides papillosus, Eimeria spp., and Strongyles, especially the Haemonchus contortus and Trichostrongylus spp. According to the issues discussed in this paper and by other authors, the prevalence and intensity of various GIPs vary with an animal's location,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…and Fasciola spp.. Various studies have been conducted on the prevalence of gastrointestinal parasitism in small ruminants in India [22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…and Fasciola spp.. Various studies have been conducted on the prevalence of gastrointestinal parasitism in small ruminants in India [22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…This result was higher than those previously reported in other regions of Peru such as Ica, where an overall prevalence of 67.6% was reported ( ). According to all these works, there is a high prevalence of STE in goat herds worldwide, which can be explained due to the high biotic potential of nematodes represented by this egg type, and their short generation interval, which allow them to proliferate and contaminate the pastures (Mpofu et al, 2022;Bowman, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Goats have the great ability to adapt to nutritional and climatic changes, in addition to contributing to the e cient management of plants and soil (Chacón-Hernández & Boschini-Figueroa, 2015). However, gastrointestinal parasite infections are one of the major problems of goat farming, being responsible for economic losses due to mortality and decreased meat and milk production, reducing the incomes of small farmers (Emiru et The prevalence of gastrointestinal parasites and intensity of infections varies depending on the local environment (temperature, rainfall, humidity, and vegetation), management practices, seasonal variations, as well as age, sex, and breed (Belina et al, 2017;Mpofu et al, 2022). Risk factors such as age, seasonality, and body condition have been reported to exhibit a signi cant association with nematodes, Moniezia spp., and Eimeria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a Cu deficiency in yaks resulted from increased levels of naturally occurring Mo in the soil and forages in China [8]. Biochemical influences on the Cu metabolism that were associated with thiomolybdates include (1) the enlarged biliary secretion of Cu from liver stores; (2) the effective requisite of Cu to plasma albumin, which results in a reduced biochemical process; and (3) the removal of Cu from metalloenzymes [9]. It has been reported that adding 3.0 g of S and 4.0 mg of Mo/kg of the diet to the basal diet that contains 1.0 g of S and 0.5 mg of Mo/kg of the diet decreased the Cu metabolism by 40 to 70% [10], while a moderately high level of S (2.7 g S/kg of the diet) in the diet, with increasing dietary Mo from 5 to 10 mg of Mo/kg of the diet, did not further reduce the Cu status in steers [11], which suggests that the synthesis of thiomolybdates may plateau with relatively moderate levels of Mo in the diet.…”
Section: Introductionmentioning
confidence: 99%